2003
DOI: 10.1117/12.514539
|View full text |Cite
|
Sign up to set email alerts
|

The next frontier for communications networks: power management

Abstract: Storage, memory, processor, and communications bandwidth are all relatively plentiful and inexpensive. However, a growing expense in the operation of computer networks is electricity usage. Estimates place devices connected to the Internet as consuming about 2%, and growing, of the total electricity produced in the USA-much of this power consumption is unnecessary. Power management is needed to reduce this large and growing energy consumption of the Internet. We see power management as the 'next frontier' in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 12 publications
0
89
0
1
Order By: Relevance
“…They apparently had not enabled the power management features after disabling them. Christensen et al (2004) also found that users disabled their power management features to ensure access to their computers at all times.…”
Section: Input Intervalsmentioning
confidence: 99%
“…They apparently had not enabled the power management features after disabling them. Christensen et al (2004) also found that users disabled their power management features to ensure access to their computers at all times.…”
Section: Input Intervalsmentioning
confidence: 99%
“…His initial work focuses on the NCP design for on-board NIC and LAN scenarios. He also analyzed the network traffic in university dormitory during idle and busy periods to forecast the NCP importance [1]. The NCP design on host's NIC, application specific wake-up, preserving TCP connections and strategies to increase the host's sleep period are addressed in [5].…”
Section: Related Workmentioning
confidence: 99%
“…Failing to generate/respond heart-beat messages will drop the network connection and results in the application state loss [6]. Thus, much of the energy consumed by the Internet connected edge devices is wasted as these applications don't transmit real data most of the time but just the periodic heart-beat messages [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy saving is only achieved when the client is completely shut-down, missing the cases of active idle or low network utilization periods, which comprise a significant part of network activity. Measurements show that the average utilization of desktop Ethernet links is in the range of 1%-5% [5], [6]. Both PBD and TWD provide major energy saving for these low network utilization periods, while maintaining high performance for high utilization bursts/periods.…”
Section: Tcp Level Power Reductionmentioning
confidence: 99%